Solve for z z/6=-10

Math
z6=-10
Multiply both sides of the equation by 6.
6⋅z6=6⋅-10
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅z6=6⋅-10
Rewrite the expression.
z=6⋅-10
z=6⋅-10
Multiply 6 by -10.
z=-60
z=-60
Solve for z z/6=-10

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top